This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f ( x ) ( 1 − x ) f ( x ) = = = = ( 1 + x ) ( 1 + x 2 ) ( 1 + x 4 ) ( 1 + x 8 ) … ( 1 − x ) ( 1 + x ) ( 1 + x 2 ) ( 1 + x 4 ) ( 1 + x 8 ) … ( 1 − x 2 ) ( 1 + x 2 ) ( 1 + x 4 ) ( 1 + x 8 ) … ( 1 − x 4 ) ( 1 + x 4 ) ( 1 + x 8 ) …
If we keep on doing this, every term collapses and we are finally left with
( 1 − x ) f ( x ) = 1 − x 2 n
Since there are infinitely many terms, n approaches infinity. Also, since 1 > ∣ 3 1 ∣ , x 2 n approaches 0. Hence we can write the equation again as
( 1 − x ) f ( x ) = 1 f ( x ) = 1 − x 1